Keterbukaan Informasi Publik: Studi Pada Keberhasilan Pemerintah Daerah Kabupaten Luwu Utara 2019 - Tawakkal Baharuddin (Jurnal Pemerintahan dan Politik Lokal, 2020)
Public information disclosure is an important aspect of realizing a good governance system. The Indonesian government, through the Law on Public Information Disclosure, continues to strive so that all public agencies can provide easy access to information. This study uses a qualitative approach with data sources derived from documentation studies, news sites, and websites. The results of this study indicate that there is a fairly positive trend in which the North Luwu Regency Government has managed to obtain the highest score for three (3) consecutive years, namely 2017, 2018, and 2019 for information disclosure with the predicate Towards Informative. This achievement is influenced by the performance of the government which continues to make various efforts, namely, socialization and training, replication of innovations, utilization of website-based networks, and the availability of Command Center facilities. This achievement is also considered to affect maximum results in the future to obtain the title of Informative in the aspect of public information disclosure